PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN RUANGOPI GALAXY KOTA BEKASI - Reina Athira; Wiwik Rachmarwi (Jurnal Manajemen Bisnis Krisnadwipayana, 2020)
This study aims to determine the effect of purchasing decisions by consumers on product quality and prices on coffee products in Ruangopi. This research is quantitative descriptive. Type of the research was descriptive verification that with the depiction and exposure variables studied and then pulled conclusion. Research variable which being independent variable was a product quality and the price as well as the purchasing decisions as the dependent variable. The population in this study were consumers who came to Ruangopi for 1 month. Sampling in this study using random sampling to 83 consumers who buy coffee in Ruangopi. Test instruments conducted with validity test and reliability test and analysis techniques used were multiple regression analysis.